Dissimilar welding of as-cast AlCoCrFeNi2.1 Eutectic high entropy alloy with 316 stainless steel and Inconel 718 - Pedro, Rodrigo Alexandre Gomes (2024)
During the last few years, high entropy alloys (HEA) have received increasing attention owing to their remarkable characteristics and mechanical properties, emerging as novel engineering alloys for multiple functional and structural applications. Recently, gas tungsten arc welding (GTAW) was suc- cessfully attempted for the first time on an AlCoCrFeNi2.1 eutectic high entropy alloy (EHEA). How- ever, dissimilar welding of EHEAs is still scarce. During the non-equilibrium fusion dissimilar welding, mixing of the liquid phases of two materials with distinct thermophysical properties can promote the generation of undesirable and detrimental phases. To bridge this gap, and pave the way for potential structural applications, GTAW technique was employed to weld the AlCoCrFeNi2.1 EHEA with 316 stainless steel and Inconel 718, aiming to obtain defect-free welded joints. The effects of the GTAW technique on the microstructure and mechanical behavior were investigated and correlated by coupling optical microscopy, microhardness mapping, tensile tests and fracture surface analysis. Both joints dis- played a heterogeneous microstructure in the fusion zone (FZ), varying from equiaxial to coarse elon- gated dendritic structures. The coarse grain morphology translated into lower hardness results across the FZ of the AlCoCrFeNi2.1 EHEA/316 stainless steel joint. Conversely, in the AlCoCrFeNi2.1 EHEA/In- conel 718 joint, a remarkable finding was the substantial increase in hardness along the molten pool, allowing to unveil a possible solid solution strengthening mechanism induced by the precipitates upon fusion of the Inconel 718. This mechanism justifies the increment in the ultimate tensile strength, com- pared to the AlCoCrFeNi2.1 EHEA/316 stainless steel joint, while preserving most of the fracture strain (653 vs 432 MPa and 9.2 vs 9.7 %, respectively). Overall, both dissimilar joints showcased a promising strength and ductility synergy, establishing the potential of GTAW for the dissimilar welding of EHEAs to traditional metals, targeting structural applications.